Sistem Informasi Penentuan Harga Pokok Produksi Pada Nirwana Collection Dengan Metode Job Order Costing - sukemi Kamto Sudibyo; Sabrina Intan Pratiwi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
Nirwana Collection is a shell craftsman in Kendal Regency. Nirwana Collection does not yet have a system for calculating the cost of production. In accounting records done manually, the data is not well organized and has not produced information as expected. Nirwana Collection produces goods based on orders, the calculation of the cost of production is still not correct, because it does not calculate other costs incurred and only focuses on raw materials. This of course results in an inaccurate selling price and results in a profit that is not as expected. The Accounting Information System for the Cost of Production at the Nirwana Collection with the Job Order Costing method can process recordings and transactions at the Nirwana Collection more effectively, as well as making it easier to produce production cost reports quickly and accurately.